THE ACUTALITY OF OBSERVING THE INTERGENETIC INTERVAL - Светлана Ивановна Елгина; Ксения Вячеславовна Кадашникова; Дарья Андреевна Мигулько; Софья Владимировна Третьякова; Вадим Гельевич Мозес; Елена Владимировна Рудаева; Кира Борисовна Мозес (The Publishing House Medicine and Enlightenment, 2022)
The intergenetic interval is the time interval between the birth of a child and the onset of the next pregnancy. WHO (2018) regulates the optimal intergenetic interval between two consecutive births lasting 24 + 9 months (the time interval between childbirth and the next conception plus 9 months of gestation). Non-compliance with AI negatively affects the course of pregnancy, the outcomes of childbirth for both the mother and the fetus.